Cryo-EM structure of cortical microtubules from human parasite Toxoplasma gondii identifies their microtubule inner proteins - Xiangli Wang; Yong Fu; Wandy L. Beatty; Meisheng Ma; Alan Brown; L. David Sibley; Rui Zhang (Nature Communications, 2021)
Cortical microtubules (MTs) in Apicomplexa are specialized MTs involved in maintaining the parasite’s shape and are, as such, unusually stable. Here, cryo-EM analysis of cortical MTs from Toxoplasma gondii offers insight into the mechanism of their stabilization by three bona fide microtubule inner proteins.